The impact of high rainfall events on the submesoscale salinity field in a coastal sea: Greater Cook Strait, New Zealand - Khushboo Jhugroo; Joanne M. O'Callaghan; Craig L. Stevens (New Zealand Journal of Marine and Freshwater Research, 2025)
River inflow into the coastal oceanic environment can result in low salinity submesoscale features (LSMFs). The enhanced water column stability sustained within these coherent structures affects local biological productivity. With‐event and seasonal variability of LSMFs were investigated in a coastal sea — Greater Cook Strait — that is characterised by strong tidal and wind forcing as well as being forced at the land‐sea boundary by several major rivers. A combination of ocean glider and satellite observations revealed the existence of seasonal variability in temperature, chlorophyll and stratification in LSMFs. High rainfall from ex‐cyclone enhanced production of LSMFs in seasons when they would otherwise be less frequent. Stronger stratification was observed at the end of spring, in summer and at the beginning of autumn both in ambient shelf conditions and within LSMFs. Subsurface chlorophyll‐a maxima were found associated with summer and spring LSMFs, when temperature had a stronger contribution to vertical stratification. In the available samples, LSMFs were advected seawards when river discharges exceeded 600 m s . When river flows were lower than this threshold, other drivers such as wind or currents were required to advect the observed LSMFs offshore.